Individual Agency and the Diversity of Traditional Practice: The Iji Nla Association of Ijede - Charles K. Omotayo (Yoruba Studies Review)
The history of the Yoruba is replete with individuals who through their activities changed the face of local tradition. In Ijede town, a suburb of Ikorodu in Ijede Local Council Development Area of Lagos State, exists the Iji Nla Association, an ancient traditional group that rose to local power through the agency of Prince Ajanaku during the first half of the twentieth century. Over time, it increasingly functioned as an institution providing traditional social control mechanisms and security. This article focuses on the origin, structure, and diversity of the Iji Nla Association as a traditional social mechanism and its continued relevance in Ijede. The methodology of this research is descriptive and analytical. It relies essentially on information from in-depth interviews and secondary sources such as books and journals.